World War II and the Rebirth and Death of Canada’s Merchant Marine - Hennessy, Michael (Journal of the Canadian Historical Association / Revue de la Société historique du Canada, 1995)
AbstractTwice before the Second World War the Canadian merchant marine had collapsed in the face of competing conceptions of empire and commercial interest. Though once home to a thriving merchant fleet, the passing of the age of sail marked Canada's decline as a maritime nation. Most of the surviving merchant fleet sailed under British registry, employing British crews and officers. During the Second World War, Canada rebuilt its merchant marine. As the war drew to a close, the state, labour and enterprise supported the framing of a Canadian maritime policy to preserve the merchant shipping capacity developed during the war.The fleet's ambiguous origins, conflicting national trade policy, the absence of a laissez-faire international shipping market, the rise of cold-war tensions and the very peculiar problems of trade to the sterling bloc savaged post-war efforts to maintain the fleet. The timing and nature of the collapse were particularly Canadian. Barriers to currency convertibility, carriage restrictions, and high labour and production costs, proved formidable obstacles which representatives of the Canadian state were very largely powerless to overcome. In combination, these elements, rather than some invisible hand, explain why Canadian ship owners led the way in abandoning their national flag and why the state helped them. Sole attribution for the death of the merchant marine should no longer fall to unfavourable labour costs or union activism.